2011
DOI: 10.1016/j.jmoldx.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of KIAA1549-BRAF Fusion Transcripts in Formalin-Fixed Paraffin-Embedded Pediatric Low-Grade Gliomas

Abstract: Alterations of BRAF are the most common known genetic aberrations in pediatric gliomas. They frequently are found in pilocytic astrocytomas, where genomic duplications involving BRAF and the poorly characterized gene KIAA1549 create fusion proteins with constitutive B-Raf kinase activity. BRAF V600E point mutations are less common and generally occur in nonpilocytic tumors. The development of BRAF inhibitors as drugs has created an urgent need for robust clinical assays to identify activating lesions in BRAF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 21 publications
0
55
1
Order By: Relevance
“…The BRAF rearrangement might not show as strong correlation as other prognostic markers for the clinical outcome of PAs. A lot of papers have reported that there are not still more reliable predictive factors for clinical aggressiveness of PAs than histological findings [4,7,8,12,14,17]. In the present case, nuclear atypia, increased MIB-1 labeling index, marked necrosis with [13]; however, some reports of anaplastic PA did not always meet the criteria [1,18].…”
Section: Discussioncontrasting
confidence: 57%
“…The BRAF rearrangement might not show as strong correlation as other prognostic markers for the clinical outcome of PAs. A lot of papers have reported that there are not still more reliable predictive factors for clinical aggressiveness of PAs than histological findings [4,7,8,12,14,17]. In the present case, nuclear atypia, increased MIB-1 labeling index, marked necrosis with [13]; however, some reports of anaplastic PA did not always meet the criteria [1,18].…”
Section: Discussioncontrasting
confidence: 57%
“…Hydrolysis probe assays to detect K-B exon junctions were designed according to Tian and colleagues and purchased from Life Technologies (Darmstradt, Germany) [15]. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA was used as internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, BRAF fusions (Horbinski et al 2010;Hawkins et al 2011) and V600E mutants characterize additional astrocytoma subsets with clinical relevance (Dias-Santagata et al 2011;Schindler et al 2011;Tian et al 2011). In contrast to the mutant IDH/G-CIMP + tumors, glioblastomas appear surprisingly distinct but significantly more complex genomically, making diagnostic subclassification schemes more challenging.…”
Section: Toward a Molecular Classification Of Gliomamentioning
confidence: 99%